2022
DOI: 10.1038/s41598-022-26133-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as the regulatory hubs in rice response to salt stress

Abstract: Salinity seriously constrains growth and fertility of rice worldwide. Long non-coding RNAs (lncRNAs) play crucial roles in plant abiotic stress response. However, salt responsive lncRNAs are poorly understood in rice. Herein, salt responsive lncRNAs (DE-lncRNAs) were identified in FL478 (salt tolerant) compared to its susceptible parent (IR29) using RNA-seq in root tissues at seedling stage. In FL478 and IR29, 8724 and 9235 transcripts with length of > 200 bp were nominated as potential lncRNAs, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…There was a clear preference for T across the entire region, except for the −25 to −10 and 0 to 10 regions, which were predominant for A, suggesting a nucleotide bias upstream and downstream of the cleavage site in 3′ UTRs ( Figure 3 C). The nucleotide bias in these sites was similar to that previously reported [ 20 ], which supports the authenticity of the identified poly(A) sites.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There was a clear preference for T across the entire region, except for the −25 to −10 and 0 to 10 regions, which were predominant for A, suggesting a nucleotide bias upstream and downstream of the cleavage site in 3′ UTRs ( Figure 3 C). The nucleotide bias in these sites was similar to that previously reported [ 20 ], which supports the authenticity of the identified poly(A) sites.…”
Section: Resultssupporting
confidence: 90%
“…Long non-coding RNAs (lncRNAs) are defined as transcripts longer than 200 bp that cannot encode a full-length protein, and the main difference between lncRNA and mRNA is the lack of coding protein sequence potential in lncRNA [ 19 , 20 , 21 ]. Recently, more and more evidence has suggested that lncRNAs have regulatory roles in various biological processes, such as development, vernalization, and environmental stress adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between stress-specific TFs and lncRNAs were hypothesized to play a significant role in response to various abiotic stresses, including salt stress (Mirdar Mansuri et al, 2022). For example, in wheat, Shumayla et al (2017) demonstrated that lncRNAs were co-expressed with the TFs related to WRKY, NAC, MYB, ERF, C3H, C2H2, bZIP, and bHLH families under salt stress conditions; several lncRNAs associated with TFs belonging to ARF, C2C2(Zn), and HSF families were found in duckweed (Fu et al, 2020); in maize, 11 target transcripts of the salt-responsive lncRNAs belonging to seven TF families, including bHLH, C2H2, Hap3/NF-YB, HAS, MYB, WD40, and WRKY, were predicted (Liu et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence is available on ncRNAs associated with the regulation of salt stress in plants [177][178][179][180][181][182][183][184][185][186][187][188][189][190], as listed in Table 1. Nearly 75 conserved miRNAs were identified from the control and NaCl-treated salt-tolerant rice varieties [180].…”
Section: Salt Stressmentioning
confidence: 99%
“…The study further identified two differentially expressed (DE)-lncRNAs, such as TCONS_00008914 and TCONS_00008749, as potential target mimics of known rice miRNAs. In another study, using another salt-tolerant rice (FL478), Mansuri et al [177,187] identified DE-lncRNA.2-FL, that showed multiple interaction with osa-miR2926 miRNA. This interaction regulates the expression of various salt-stress-responsive genes, such as chloride channel protein, potassium transporter, and some genes involved in sensing and signaling, such as cysteine-rich receptor-like protein kinase 8 precursors and serine/threonine protein kinase.…”
Section: Salt Stressmentioning
confidence: 99%